2016
DOI: 10.5009/gnl15321
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Model for Predicting Hepatocellular Carcinomas in Patients with Post-Sustained Virologic Responses of Chronic Hepatitis C: A Case Control Study

Abstract: Background/AimsNo clinical model exists to predict the occurrence of hepatocellular carcinoma in sustained virologic response-achieving (HCC after SVR) patients with chronic hepatitis C (CHC).MethodsWe performed a case-control study using a clinical database to research the risk factors for HCC after SVR. A predictive model based on risk factors was established, and the area under the receiver operating characteristic curve (AUC) was calculated.ResultsIn the multivariate model, an initial diagnosis of compensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In the IFN era, the incidence of HCC in SVR-achieving or even in antiviral-treated hepatitis C patients is very low [6]. Our previous study [7] reported that the overall rate of HCC after SVR was 1.2% (26/2,130) during a median post-SVR time of 17.5 months at The First Affiliated Hospital of Zhengzhou University and Beijing 302 Hospital, which are the largest tertiary general hospital (containing 11,000 clinical beds) and the largest liver disease hospital (containing 1200 clinical beds) in China, respectively. However, the unexpectedly high incidence of HCC in the DAA era is in sharp contrast to that in the former interferon era.…”
Section: Unexpected High Incidence Of Hepatocellular Carcinoma In Pat...mentioning
confidence: 90%
See 1 more Smart Citation
“…In the IFN era, the incidence of HCC in SVR-achieving or even in antiviral-treated hepatitis C patients is very low [6]. Our previous study [7] reported that the overall rate of HCC after SVR was 1.2% (26/2,130) during a median post-SVR time of 17.5 months at The First Affiliated Hospital of Zhengzhou University and Beijing 302 Hospital, which are the largest tertiary general hospital (containing 11,000 clinical beds) and the largest liver disease hospital (containing 1200 clinical beds) in China, respectively. However, the unexpectedly high incidence of HCC in the DAA era is in sharp contrast to that in the former interferon era.…”
Section: Unexpected High Incidence Of Hepatocellular Carcinoma In Pat...mentioning
confidence: 90%
“…First, the indications of anti-HCV therapy have largely expanded during the era of DAAs [2,8]. As in prior reports [6,7], older age and the presence of cirrhosis at SVR or initiation of treatment were two important factors related to the development of HCC after SVR. We have sound reasons to believe that relatively older and more advanced cirrhotic patients are currently receiving and will receive DAA therapy in the future.…”
Section: Unexpected High Incidence Of Hepatocellular Carcinoma In Pat...mentioning
confidence: 99%